CREATIVITY AND CREATIVE TASKS FOR LANGUAGE LEARNERS - Tan Bee Tin (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
'Creativity', i.e. the human ability and need to make new meaning, can help learners to destabilise, explore and transform their langrage, a desirable goal in language teaching. In this talk, I propose a 'creative' view of language as a tool for creating new ideas and meaning. In order to increase the learner's desire to explore and retrieve less accessible language within and beyond their Zone of Proximal Development, I will propose two conditions for creative language learning tasks: 1 creating the need to say something new and 2. setting up constraints in language learning tasks in order to encourage learners to explore and transform their language. Too much freedom can restrict possibilities for learners to explore and broaden their language repertoire as learners may retrieve safe options and make familiar choices.